Intakes of long-chain omega-3 polyunsaturated fatty acids and non-fried fish in relation to incidence of chronic kidney disease in young adults: a 25-year follow-up - Park, Inwhee (Eur J Nutr, 2019)
PURPOSE: The prevalence of chronic kidney disease (CKD) is increasing rapidly in many countries and has become a major public health concern. Although intakes of long-chain omega-3 polyunsaturated fatty acids (LCω3PUFA) and its food source — fish — may have renal protective effects, little is known about the longitudinal association between these dietary factors and CKD incidence. METHODS: A total of 4133 healthy individuals of black and white race aged 18 to 30 at baseline (1985–86) from the Coronary Artery Risk Development in Young Adults study were enrolled and followed up over 25 years. LCω3PUFA and fish intake were assessed by an interview-based dietary history questionnaire at baseline, year 7 (1992–93), and 20 (2005–06). RESULTS: Four hundred eighty-nine incident cases of CKD were identified. After adjustment for potential confounders, LCω3PUFA intake was inversely associated with CKD incidence [HR = 0.73 (95% CI: 0.60 to 0.89), P = 0.002, with one standard division (0.19 g/day) increment in LCω3PUFA], This inverse association was persisted among females [0.64 (95% CI: 0.48, 0.84; P = 0.002], but not males (P(interaction) = 0.070). A marginal significant inverse association was also found between non-fried fish consumption and CKD incidence (HR = 86, 95% CI: 0.73, 1.01; P= 0.073). CONCLUSIONS: Dietary LCω3PUFA intake was inversely associated with incidence of CKD among American young adults over 25 years of follow-up. The suggestive evidence of the inverse association between non-fried fish consumption with CKD incidence needs further confirmation.